Money as the material support for the dispute for the sense of the nation: a study of argentinean peso from a semiotic perspective (Estudios Sociales, 2023)
In May 2022, the government headed by Alberto Fernández presented new designs for the Argentine peso banknotes. This event reactivated a semiotic-discursive dispute existing in Argentina over the iconography to be used in the design of the national currency. Over the last 25 years, this dispute has oscillated between strategies that prioritise the inclusion of personalities and historical events and those that prioritise the inclusion of natural landscapes and specimens of fauna considered autochthonous. This article studies from a semiotic perspective the two local encyclopaedias in conflict in this dispute and argues how currency can be a space of dispute for the meaning of the nation.
Keywords: Money; Currency; Argentina; Argentinean Peso; National identity